Model Manajemen Pendidikan Untuk Mengembangkan Kemandirian Siswa Melalui Project-Based Learning - Saepudin Saepudin; Riki Faisal; Agus Jaenal; Rendi Atnanto; Wiwin Winarti (Departement of Mathematics Education, 2024)
Student independence is a very important skill in education, especially at the elementary school level, to prepare them to face future challenges. This research aims to determine the effect of implementing the Project-Based Learning (PjBL) model on the development of student independence at SDIT Al-Anshoriyah. PjBL was chosen because it was considered able to teach students to be more independent in managing time, completing assignments, collaborating with friends, and taking initiative. The research method used is descriptive research with a quantitative approach. Data collection techniques were carried out through observation, interviews, and distributing questionnaires to students and teachers. The data obtained was analyzed using descriptive statistics to determine the increase in student independence before and after implementing PJBL. The research results show that implementing PjBL can increase students' independence in managing time, completing assignments, collaborating with friends, and taking initiative. This increase looks significant, where the percentage of students who are able to manage their time well increases from 55% to 78%, and the ability to collaborate with friends increases from 65% to 85%. The implications of this research are the importance of more intensive training for teachers in designing and implementing projects, as well as the need for better managerial support for implementing PjBL